2016
DOI: 10.1038/nn.4265
|View full text |Cite
|
Sign up to set email alerts
|

Genetically targeted magnetic control of the nervous system

Abstract: Optogenetic and chemogenetic actuators are critical for deconstructing the neural correlates of behavior. However, these tools have several limitations, including invasive modes of stimulation or slow on/off kinetics. We have overcome these disadvantages by synthesizing a single component, magnetically sensitive actuator, “Magneto,” comprised of the cation channel, TRPV4, fused to the paramagnetic protein, ferritin. We validate non-invasive magnetic control over neuronal activity by demonstrating remote stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
245
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(255 citation statements)
references
References 49 publications
7
245
2
1
Order By: Relevance
“…Also, the identified mechanoelectrical effects are dominant in the short time scales considered here, but in conjunction with parallel thermal effects like changes in the Q 10 factor [47], probably play a significant role under a wide array of thermal modulation scenarios [48]. Related insights may also help guide our understanding of other emerging neurophysical modalities like magnetogenetic stimulation (whose biophysics is still poorly understood [49,50]). For example, we note that membrane mechanoelectrical effects involving dimensional changes were suggested in other contexts involving changes in intramembranal forces, including action potential-related intramembrane thickness variations [51][52][53] and ultrasoundinduced formation of intramembrane cavities (or "bilayer sonophores" [54]).…”
Section: Discussionmentioning
confidence: 74%
“…Also, the identified mechanoelectrical effects are dominant in the short time scales considered here, but in conjunction with parallel thermal effects like changes in the Q 10 factor [47], probably play a significant role under a wide array of thermal modulation scenarios [48]. Related insights may also help guide our understanding of other emerging neurophysical modalities like magnetogenetic stimulation (whose biophysics is still poorly understood [49,50]). For example, we note that membrane mechanoelectrical effects involving dimensional changes were suggested in other contexts involving changes in intramembranal forces, including action potential-related intramembrane thickness variations [51][52][53] and ultrasoundinduced formation of intramembrane cavities (or "bilayer sonophores" [54]).…”
Section: Discussionmentioning
confidence: 74%
“…Our argument is hence similar to thermo/magneto-genetics where it is expected that the applied heat or mechanical stimuli might also activate intrinsic heat/mechano-sensitive ion channels. [170][171][172][173] Although there is a possibility that other mechano-sensitive ion channels might be activated by magnetic forceinduced stretching of lipid membrane, we showed that the contribution by N-type Ca 2+ channels was the largest (Fig. 5g).…”
Section: Mechanism Of Stimulationmentioning
confidence: 76%
“…Next, we monitored the expression of TRPV4 which is the only type of mechano-sensitive ion channel other than N-type calcium channel that has been reported for neural stimulation. 173 However, chronic stimulation did not affect the expression of TRPV4 (Appendix B Fig. 2a-b).…”
Section: Calcium Dye Incubation and Magnetic Force Stimulationmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, in neuroscience, magnetogenetics was recently reported as a promising noninvasive technique to control gene expression and cellular activity in vivo (Etoc et al, 2013;Etoc et al, 2015;Long et al, 2015;Stanley et al, 2015;Stanley et al, 2016;Wheeler et al, 2016). It shows many advantages over the currently widely used techniques such as deep-brain stimulation and optogenetics (Wichmann and Delong, 2006;Zhang et al, 2011), which require surgical implantation of a wire electrode or optical fiber (Kringelbach et al, 2007;Häusser, 2014).…”
Section: Introductionmentioning
confidence: 99%